Release of volatile compounds from sliced onion analysed by gas chromatography coupled to mass spectrometry and its antimicrobial activity - Machová, Martina; Bajer, Tomáš; Šilha, David; Ventura, Karel; Bajerová, Petra (VÚP Food Research Institute NAFC, 2019)
Plants belonging to the genus Allium are known for their high content of organosulfur compounds, which give them typical flavour and aroma released during their processing. These plants are also known for various biologically important effects, in particular antimicrobial activity. The volatile compounds are released enzymatically after rupture of the plant cells. The released volatile organosulfur compounds of onion and their monitoring in time was done by using headspace solid phase microextraction coupled to gas chromatography-mass spectrometry (HS-SPME/GC-MS). Nineteen organosulfur compounds were identified with different course of release. The main released compounds were thiopropanal S-oxide, methylprop(en)yldisulfide and prop(en)yltrisulfide. Antimicrobial activity of onion juice was tested on 8 microorganisms using disc-diffusion and well-diffusion methods. Completely resistant microorganisms were Escherichia coli, Pseudomonas aeruginosa and Bacillus subtilis, the most sensitive was Candida albicans.
Analýza těkavých látek uvolňovaných z cibule po jejím nakrájení pomocí plynové chromatografie s hmotnostní detekcí a jejich antimikrobiální aktivita
Keywords: onion; organosulfur compounds; headspace solid phase microextraction; antimicrobial activity; cibule; organické sloučeniny síry; headspace mikroextrakce tuhou fází; antimikrobiální aktivita